1989
DOI: 10.1038/341705a0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional crystal structures of Escherichia coli met repressor with and without corepressor

Abstract: The three-dimensional crystal structure of met repressor, in the presence or absence of bound corepressor (S-adenosylmethionine), shows a dimer of intertwined monomers, which do not have the helix-turn-helix motif characteristic of other bacterial repressor and activator structures. We propose that the interaction of met repressor with DNA occurs through either a pair of symmetry-related alpha-helices or a pair of beta-strands, and suggest a model for binding of several dimers to met operator regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(132 citation statements)
references
References 27 publications
6
125
0
Order By: Relevance
“…These results suggested that a complex of MetJ and SAM binds a common nucleotide sequence in the promoters of target genes to prevent their transcription (Greene et al, , 1973Hobson & Smith, 1973). Identification of a consensus repressor binding site ('met box'; Belfaiza et al, 1986) and crystallographic studies (Rafferty et al, 1989) all support this model. Genes most induced by defects in either metJ or metK include metA, B, C, E, F, K, L (as the downstream gene in the metBL operon) and metR (a regulatory protein that, by itself or when bound with homocysteine, regulates expression of a variety of genes in the met regulon to coordinate the activities of the two branches of the methionine biosynthetic pathway; again, see Greene, 1996).…”
Section: Introductionsupporting
confidence: 48%
“…These results suggested that a complex of MetJ and SAM binds a common nucleotide sequence in the promoters of target genes to prevent their transcription (Greene et al, , 1973Hobson & Smith, 1973). Identification of a consensus repressor binding site ('met box'; Belfaiza et al, 1986) and crystallographic studies (Rafferty et al, 1989) all support this model. Genes most induced by defects in either metJ or metK include metA, B, C, E, F, K, L (as the downstream gene in the metBL operon) and metR (a regulatory protein that, by itself or when bound with homocysteine, regulates expression of a variety of genes in the met regulon to coordinate the activities of the two branches of the methionine biosynthetic pathway; again, see Greene, 1996).…”
Section: Introductionsupporting
confidence: 48%
“…This prediction holds for all papillomavirus E2 proteins sequenced to date. Although there is no primary sequence similarity between the 333-344 DNA contact region and the DNA contacting p-strand portions of the Met or Arc repressors (Rafferty et al 1989;Breg et al 1990), we suspect that E2 may fold similarly at its point of interaction with DNA. Although these models suggest folding as extended peptide, an a-helical conformation is also possible as proline is absent from this region.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the RHH family are much smaller proteins, ranging from the 45-residue CopG repressor to the 133-residue NikR from E. coli, with variations caused by additional N-or C-terminal domains (17,30). Examples of C-terminal functional regions in RHH members include protein tetramerization in the Mnt repressor, binding of the corepressor S-adenosylmethionine in MetJ, binding of the ParE toxin protein in the ParD repressor, and nickel binding by the repressor NikR (31)(32)(33)(34)(35)(36). In NikR, a C-terminal nickel-binding domain is attached to an N-terminal RHH fold (36).…”
Section: Discussionmentioning
confidence: 99%